2001
DOI: 10.1302/0301-620x.83b8.11754
|View full text |Cite
|
Sign up to set email alerts
|

Oral vitamin C attenuates acute ischaemia-reperfusion injury in skeletal muscle

Abstract: I schaemia-reperfusion injury (IRI) is caused by endothelial and subendothelial damage by neutrophil-derived oxidants. Vitamin C is an antioxidant which attenuates endothelial injury after IRI. Our aim was to evaluate the effect of oral vitamin C in the prevention of IRI in skeletal muscle. We used a model of cross-clamping (3 hours) and reperfusion (1 hour) of the cremaster muscle in rats. Muscle function was assessed electrophysiologically by electrical field stimulation. Infiltration by neutrophils was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Restoration of blood flow to an acutely ischemic limb initiates a cascade of cellular and biochemical events that result in muscle edema, necrosis, and impaired muscle function (Kearns et al 2001). The associated lung injury is mediated by the adherence of activated neutrophils to the endothelium of the pulmonary microvasculature, resulting in spillage of protein-rich transudate into the alveolar spaces-hallmarks of the acute respiratory distress syndrome (ARDS) (Barry et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restoration of blood flow to an acutely ischemic limb initiates a cascade of cellular and biochemical events that result in muscle edema, necrosis, and impaired muscle function (Kearns et al 2001). The associated lung injury is mediated by the adherence of activated neutrophils to the endothelium of the pulmonary microvasculature, resulting in spillage of protein-rich transudate into the alveolar spaces-hallmarks of the acute respiratory distress syndrome (ARDS) (Barry et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the previous work on skeletal muscle ischemia reperfusion injury has focused on the effects of pretreatment with various agents (Kearns et al 2001). While this is important to further our understanding of this complex process and to elucidate the underlying mechanisms involved, this does not always correlate with the clinical setting where ischemia is often a sudden unpredictable event.…”
Section: Discussionmentioning
confidence: 99%
“…Kearns et al [15] found that after 30 min infrarenal aortic cross-clamping and 120 min reperfusion in I/R injury protects against I/R-induced acute lung injury by vitamin C therapy. Still, Kearns et al [29] documented that pretreatment with oral vitamin C relieves endothelial injury against acute muscle I/R injury as an antioxidant agent possibly by attenuating neutrophil respiratory burst activity. Herbaczynska-Cedro et al [30] demonstrated that vitamin C reduces oxygen free radicals production in human circulating neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst all antioxidants, ascorbate appears to be the most attractive option for treating and preventing IRI in the lung [20,21] and other organs [24][25][26][27][28][29]. Ascorbate administration has been shown to reduce oxidative damage in endothelial cells [30,31], improve tissue perfusion [32], inhibit tumor necrosis factor α (TNFα) [33], reduce mitochondrial swelling and damage [27], preserve mitochondrial respiration [34], reduce edema [35], reduce proinflammatory chemokine expression [36], and reduce oxidative damage [37,38].…”
Section: Introductionmentioning
confidence: 99%